Effect of glutathione S‐transferase genetic polymorphisms on busulfan pharmacokinetics and veno‐occlusive disease in hematopoietic stem cell transplantation: A meta‐analysis. Issue 6 (25th December 2018) - Kim, Myeong Gyu; Kwak, Arim; Choi, Boyoon; Ji, Eunhee; Oh, Jung Mi; Kim, Kyungim
Abstract: This meta‐analysis was conducted to derive an integrated conclusion about the influence of glutathione S‐transferase (GST) genetic polymorphisms on busulfan pharmacokinetic (PK) parameters and veno‐occlusive disease (VOD). Studies which analysed the effect of GST genetic polymorphisms on area under the curve (AUC), clearance (CL) or VOD were searched for and selected. A pooled analysis was conducted using Comprehensive Meta‐Analysis programme. Nineteen studies were included in this meta‐analysis. GSTA1 *B and GSTM1 null genotypes significantly decreased CLIV of busulfan (standardized difference in means (SDM) = −1.103; P  = 0.019 and SDM = −0.418; P  = 0.002, respectively). GSTA1 *B significantly increased AUCIV of busulfan (SDM = 0.832; P  = 0.046), whereas GSTM1 did not (SDM = 0.155; P  = 0.478). The PK parameters of oral busulfan did not differ according to GST genotype. GSTA1, GSTM1 and GSTP1 were not significantly associated with VOD occurrence. GSTA1 and GSTM1 genotypes affected CLIV of busulfan, but only GSTA1 affected AUCIV . There was no significant difference in the PK parameters of oral busulfan (CLPO and AUCPO ) and VOD when only GST genotypes were considered.